Assessing the Impact of Macroeconomic Variables on Project-Based Sukuk in Indonesia - Primayanti, Yuanisa Maulina; *, Marwini (International Journal of Islamic Business and Economics (IJIBEC), 2023)
This study is aimed at examining the influence of variables such as Infrastructure Budget, Bank Indonesia Rate, Money Supply, and Bank Indonesia Sharia Certificate on Project-Based Sukuk over short and long-term periods. The research also evaluates the response given by Project-Based Sukuk to shocks in these variables, as well as their contributions to variations in Project-Based Sukuk. The Vector Error Correction Model (VECM) method, implemented through Eviews 10, was utilized in this study which employed monthly secondary data spanning the period 2016-2020. The findings suggest that, in the short term, the Infrastructure Budget variable positively affects PBS. Conversely, in the long term, the Money Supply variable negatively influences PBS. BI rate and Bank Indonesia Sharia Certificate variables appear to have no significant effect on PBS in either the short or long term. The Impulse Response Function test reveals that PBS responds positively to shocks in the Infrastructure Budget, negatively to shocks in the Bank Indonesia Sharia Certificate, and variably to shocks in the BI Rate and Money Supply. The Forecasting Error Variance Decomposition test indicates that PBS exerts the most significant influence on variance explanation. Sukuk is proposed as a viable alternative to bridge the financing gap for infrastructure development. The government is therefore urged to preserve economic stability, particularly concerning the Infrastructure Budget from the State Budget and the Money Supply, given their impact on sukuk development, which is crucial for infrastructure progression in Indonesia.